Coding to create and communicate - Lyons, Heather (Heather K.) (Lyons, Heather (Heather K.). Kids get coding., 2018)
"From sending messages to creating music, computers are used in many ways. Through fun activities, simple graphics, and clear text, this book shows readers not only what computers are used for but how these different applications work. Readers will also be reminded about responsible and safe ways to use computers."--